2015
DOI: 10.1093/ajh/hpv185
|View full text |Cite
|
Sign up to set email alerts
|

Drug Side Effect Symptoms and Adherence to Antihypertensive Medication

Abstract: Antihypertensive drug side effects was associated with drug adherence but only excessive urination and decrease in sexual drive significantly predicted lower adherence. These symptoms could be used as markers to screen out patients at high risk of non-adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 36 publications
2
86
0
2
Order By: Relevance
“…Previously, we have shown that hypertensive patients who experienced ≥4 drug-related side effect symptoms were more likely to become non-adherers (PCAR<80%). 21 Also, it has been found that a high percentage of patients (85%) who experience drug related side effects share their concerns about side effects with their physicians. 31 This suggests that patients with side effects may be also more open to admit not taking medication as prescibed, since they may not perceive a lack of adherence as their personal failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we have shown that hypertensive patients who experienced ≥4 drug-related side effect symptoms were more likely to become non-adherers (PCAR<80%). 21 Also, it has been found that a high percentage of patients (85%) who experience drug related side effects share their concerns about side effects with their physicians. 31 This suggests that patients with side effects may be also more open to admit not taking medication as prescibed, since they may not perceive a lack of adherence as their personal failure.…”
Section: Discussionmentioning
confidence: 99%
“…This scoring approach has been successfully used in previous studies among hypertensive patients. 20, 21 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Males are more likely to show low adherence rates, as the youngers, especially in resistant hypertension [23]. Also, the presence of depression and chronic heart disease are associated to lower drug adherence [30].…”
Section: Resultsmentioning
confidence: 99%
“…The unifactorial causality relationship has still a very relevant symbolic presence in most of population: One cause, one disease and one treatment, opposing the current multifactorial approach, that justifies the multiple and different combinations. Another factor in accounting is the drug-related side effects as fatigue, headache, peripheral oedema, cough, allergy, polyuria, erectile and libido dysfunction and metabolic changes, some of them very uncomfortable for patients [23]. many times inefficient are problems relevant to medical adherence.…”
Section: Strategies To Improve Adherence To Medications In Hypertensimentioning
confidence: 99%